Metodologias facilitadoras na Educação Física : Objetivando o desenvolvimento social e o autodomínio emocional - Weiss Ferraz de Oliveira, Alessandra (Educación Física y Ciencia.)
The use of strategies and the repertoire of emotions learned over the years provided emotional maturation of training individuals. But the mental structure has undergone changes, the high level of school and professional demands, the decrease in sports practice and the lower social life have triggered stress damage in adolescents. Thus, school Physical Education during adolescence can be fundamental for the maturation of the emotional skills of empathy and self-control, which are responsible for the development of emotional self-control. The aim of this research was to present possible facilitating methodologies for emotional learning, specifically for the development of emotional and social self-mastery, during the teaching-learning process at school Physical Education. In this perspective, the present research is characterized as bibliographic research. The analysis involved the works of the authors Brearley (2004) and Alzina et al. (2009), which allowed the visualization of emotional learning in teaching practice. From these works, we reconstruct possibilities that can be facilitators in the methodology for the school Physical Education teacher and, consequently, for the integral formation of the student.